Enhancing School Counselor Research and Practice in Data-Based Assessment Through Single-Case Research Design. (2nd January 2017) - Cook, Amy L.; Codding, Robin S.; Silva, Meghan; Hayden, Laura
Abstract: School counselors are increasingly called upon to implement evidence-based practice interventions and demonstrate their outcomes. Pre-/posttest designs are helpful in assessing intervention efficacy but do not provide progress monitoring as interventions unfold. This article describes ways to enhance school counselor skills in data-based assessment using single-case research design (SCRD), an underutilized design by school counselors that has demonstrated success to inform intervention in related fields. Examples of SCRD are provided, including application to professional practice and research. Implications of employing SCRD in school counseling practice as a research design that enhances data-based decision-making are also explored.